Dupuytren's Disease: A Novel Minimally Invasive Pull-Through Technique - Maruccia, Michele; Tedeschi, Pasquale; Sisto, Francesco; Converti, Ilaria; Giudice, Giuseppe; Elia, Rossella (Archives of Plastic Surgery, 2024)
Background Dupuytren's disease decreases quality of life significantly and often requires surgical treatment, nevertheless there is no actual gold standard. The aim of this study was to introduce the use of minimally invasive pull-through technique.Methods From 2016 to 2020, 52 patients suffering from Dupuytren's contracture were treated with the minimally invasive pull-through technique. We evaluated the improvement in range of motion, pain, disability, and quality of life in the long term. Total extension deficit, quick disabilities of the arm, shoulder, and hand (QuickDASH), and EuroQol five dimensions—five levels index were systematically scored before each surgical intervention and reevaluated after 24 months.Results Fourteen patients (26.9%) had already received a previous intervention (percutaneous needle aponeurotomy or collagenase Clostridium histolyticum). The mean preoperative total active extension deficit was 84.0 ± 23.3 degrees (55–130 degrees). Mean follow-up was 36 months. There were no cases of tendon rupture or neurovascular injury. Total active extension deficit at the final follow-up was 3.4 ± 2.3 degrees (0–12 degrees). The mean active range of motion of the MCP and PIP joints were, respectively, 90.5 ± 3.3 degrees (85–96 degrees) and 82.7 ± 2.5 degrees (80–87 degrees). At 24 months after cord excision, a mean 10.7 points improvement in the QuickDASH questionnaire was registered (p < 0.001). Pull-through technique was equally effective both on patients with a primary or a recurrent disease. Eight patients (15.4%) had a recurrence of disease in the metacarpophalangeal joint or proximal interphalangeal joint.Conclusion The pull-through technique is a simple, accessible, and effective technique for the treatment of Dupuytren's contracture. The use of palmar mini-incisions combined with minimal dissection has a low risk of iatrogenic injury to the neurovascular bundles and tendons, and has a low risk of recurrence rate. This study reflects level of evidence IV.
Keywords: Dupuytren; fasciectomy; pull-through; minimally invasive; recurrence